Analisis Gaya Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas VI di SD Negeri 2 Pengkelak Mas Tahun Pelajaran 2019/2020 - Suaebun, Suaebun (FAKULTAS TARBIYAH, 2020)
This study aims to: (1) describe student learning styles in Indonesian subjects (2) describe what factors influence student learning styles in Indonesian subjects (3) describe the efforts made by teachers in student learning styles in language subjects in Indonesia. This study uses a descriptive qualitative approach. The method used is observation, interviews, and documentation. The data analysis technique used is using data analysis techniques using the Miles and Huberman model, namely data reduction, data display, and drawing conclusions. The results of this study indicate that: First, the learning styles of students at SD Negeri 2 Pengkelak Mas, Sepauk District have three types of learning styles, namely visual, auditory and kinesthetic, and the most dominant learning style used is the visual learning style. Second, the factors that influence students' learning styles in Indonesian language learning are internal and external, the dominant factor is external, this is because students are more influenced by the external environment such as their families, namely, students' lack of motivation to learn. School factors, namely from schools, teachers do not use the media in teaching, and factors from the community related to the external environment, namely the lack of community support for student learning. Third, the efforts that the teacher can do are the teacher approaches the students, using the lecture method, question, and answer, and discussion, the teacher trying to condition the learning situation well.